Jamasan Kendeng as a Religious Moderation Practice for Environmental Protection - Falaq, Yusuf (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study examines the Jamasan Kendeng ritual in Central Java as a unique model of organic religious moderation emerging from local wisdom and environmental praxis. This research is qualitative with a type of ethnography. The research data is in the form of the Jamasan Kendeng ritual carried out by the community in the Kendeng Mountains. Data collection techniques were done through in-depth observation, interviews, and documentation. The data analysis technique uses with interactive model; 1) data reduction based on three theoretical frameworks (religious moderation – environmental conservation – cultural transmission); 2) a 3-dimensional integrative matrix (religious values – ecology – generation); verification with thematic and narrative analysis to construct meaning across generations. The research reveals how this ritual syncretizes Islamic values with indigenous Javanese traditions to foster interfaith tolerance (evidenced by 7.3% non-Muslim participation) and ecological conservation, demonstrated by a 46.7% increase in water discharge and successful resistance against extractive industries. While facing a crisis in traditional leadership succession, the ritual demonstrates remarkable adaptability through youth-driven digital hybridization, including e-sesaji (digital offerings) and environmental apps, with 86% of young respondents supporting its conservation ethos while reinterpreting its sacred meanings. The study concludes that Jamasan Kendeng embodies "ecological religious moderation", a grounded framework where moderation evolves from community-based environmental struggles rather than top-down doctrinal approaches, offering valuable insights for sustainable development and religious harmony in the Global South.